Striatal sensitivity to reward deliveries and omissions in substance dependent patients - Bjork, James M.; Smith, Ashley R.; Hommer, Daniel W. (NeuroImage (Orlando, Fla.), 2008)
Some motivational theories of substance dependence (SD) posit either pathologically increased or decreased ventral striatum (VS) recruitment by cues for nondrug rewards. The incentive-sensitization hypothesis, alternatively, attributes SD to enhanced incentive salience of drug-predictive cues specifically, with no requirement for altered nondrug incentive processing. We assessed whether individuals undergoing inpatient therapy for SD are characterized by altered recruitment of mesolimbic incentive neurocircuitry by cues and deliveries of nondrug rewards. During functional magnetic resonance imaging, substance-dependent patients (SDP) and controls performed a modified monetary incentive delay task featuring: a) anticipatory cues that signaled opportunities to respond to a target to either win money or avoid losing money, b) notifications of wins and losses, and c) unexpected replacement of reward trial outcomes with a demand to repeat the trial. Both anticipatory reward cues and loss cues elicited similar mood responses and VS activation between SDP and controls. However, in SDP (but not controls), reward notifications also activated VS and mesial frontal cortex, and loss notifications activated anterior insula. Finally, substitution of expected outcomes in reward trials with notifications to repeat the trial deactivated the VS in SDP but not in controls. These data do not suggest that SD is characterized by altered recruitment of VS circuitry by cues for nondrug incentives. Rather, SDP may instead have increased limbic system sensitivity to reward and loss delivery, consistent with the role of impulsivity in SD.